Liikettä ja viestintää ilmaisevien verbien rektiosta uusassyriassa ja arameassa - Kataja, Laura (1986)
On the Rection of Verbs Denoting Motion and Communication in Neo-Assyrian and Aramaic; M. A. Thesis. University of Helsinki; Supervisors: S. Parpola, T. Harviainen; in Finnish.